Czym jest Bitcoin? - Sieroń, Arkadiusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The aim of this paper is to answer the question of what — from an economic point of view — is Bitcoin. For this purpose, we make a literature review, discussing different views on the subject. Using the typology of money developed by Mises, we find that Bitcoin is a private fiat money, without, however, disproving the regression theorem. Based on the analysis, we conclude that the gold,which is a commodity money, would be a better candidate to serve as a global medium of exchangein a free market. Thus, we see the future of Bitcoin in payment system allowing to make low-cost, relatively anonymous and secure transactions, especially the foreign ones
Keywords: teoria pieniądza; pieniądz fiducjarny; bitcoin